2022
DOI: 10.1080/22221751.2022.2088406
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of heterologous boosting against SARS-CoV-2 using a recombinant interferon-armed fusion protein vaccine (V-01): a randomized, double-blind and placebo-controlled phase III trial

Abstract: Waning of neutralizing titres along with decline of protection efficacy after the second dose of COVID-19 vaccines was observed, including China-made inactivated vaccines. Efficacy of a heterologous boosting using one dose of a recombinant SARS-CoV-2 fusion protein vaccine (V-01) in inactivated vaccine-primed population was studied, aimed to restore the immunity. A randomized, double-blind and placebo-controlled phase III trial was conducted in healthy people aged 18 years or older in Pakistan and Malaysia. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
(43 reference statements)
0
15
1
Order By: Relevance
“…Since more than 95% of vaccines administered in mainland China currently are inactivated virus vaccines, we assume that all vaccinees would receive inactivated virus vaccines (namely, BBIBP-CorV or CoronaVac) for the first three doses. The IC50 neutralising antibody (Ab) titres against Omicron after the first three doses were obtained from the Brazilian study RHH-001 6 and the Phase-3 trial of V-01 vaccine 20 .…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Since more than 95% of vaccines administered in mainland China currently are inactivated virus vaccines, we assume that all vaccinees would receive inactivated virus vaccines (namely, BBIBP-CorV or CoronaVac) for the first three doses. The IC50 neutralising antibody (Ab) titres against Omicron after the first three doses were obtained from the Brazilian study RHH-001 6 and the Phase-3 trial of V-01 vaccine 20 .…”
Section: 3mentioning
confidence: 99%
“…RBD dimer-IFN-Pan Fc fusion protein) developed by Livzon. In the Phase-3 trial of 10,218 participants in Pakistan and Malaysia with a follow-up period of 60-90 days, the vaccine efficacy of V-01 as the third dose was 64% (23-83) and 39% (3-62) against Omicron infection among 4,935 participants who had received BBIBP-CorV or CoronaVac vaccines in their primary course 20 . 2) NVSI-06-08 is a recombinant COVID-19 vaccine based on the antigen of a mutation-integrated trimetric RBD developed by Sinopharm.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, data should be interpreted with caution since the safety and immunogenicity profiles were concluded based on a relatively small sample size. The phase III booster study of V-01 with a larger sample size can provide further evidence regarding this matter [ 31 ]. In addition, analysis of cellular mediated immunity was not reported which was readily able to cross recognize VOCs [ 32 , 33 ] and provide protection from severe outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of phase 1 clinical trials have shown the vaccine’s immunogenicity, its ability to induce high titers of neutralizing antibodies and its safety and good tolerability [ 125 ]. The V-01 vaccine is currently undergoing phase 3 clinical trials and has been shown to induce sustained humoral immunity in study participants vaccinated with the inactivated vaccine (NCT05096832) [ 127 ]. It has been approved for use in China.…”
Section: Recombinant Covid-19 Vaccinesmentioning
confidence: 99%